A service free wireless sensor solution - Lim, Nicole Si Ning (Nanyang Technological University, 2020)
This project includes the design and development of a service free wireless sensor system for indoor air quality monitoring, utilising energy harvesting methodology to power the system. The system detects physical quantities in the environment and uploads them into a monitoring network for further analysis. The project examines various components and techniques to design and implement the system. After careful investigation, detailed justification is given for the choice of each component and methodology. All relevant information regarding the design and development of this project is included in this report.